1999
DOI: 10.1088/0953-8984/11/6/004
|View full text |Cite
|
Sign up to set email alerts
|

Structure of molten lanthanum and cerium tri-halides by the method of isomorphic substitution in neutron diffraction

Abstract: The total structure factors of the molten trivalent metal halides MX3, where M3+ denotes La3+ or Ce3+ and X- denotes C1-, Br- or I-, have been measured by using neutron diffraction. Difference function methods were then applied on assuming that the LaX3 and CeX3 melts for a given halide ion are isomorphic. The results which follow from this assumption show that the first sharp diffraction peak in the measured total structure factors arises from cation correlations and its movement to lower scattering vector va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 46 publications
1
69
1
1
Order By: Relevance
“…This is presumably because the spectra analysed by using stronger damping factors create larger uncertainties in the coordination numbers, while this procedure helps in smoothing the diffraction data. The light rare earth ions are surrounded by more than six chlorides in pure molten chlorides as suggested by the recent neutron diffraction isomorphic substitution experiments on molten LaCl 3 [4,5]. Also, the molecular dynamics simulations with polarisable ion model have been found recently to satisfactorily reproduce the experimental diffraction pattern obtained without using any damping factor; the results showing a coordination number >6 in the liquid phase [6,7].…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…This is presumably because the spectra analysed by using stronger damping factors create larger uncertainties in the coordination numbers, while this procedure helps in smoothing the diffraction data. The light rare earth ions are surrounded by more than six chlorides in pure molten chlorides as suggested by the recent neutron diffraction isomorphic substitution experiments on molten LaCl 3 [4,5]. Also, the molecular dynamics simulations with polarisable ion model have been found recently to satisfactorily reproduce the experimental diffraction pattern obtained without using any damping factor; the results showing a coordination number >6 in the liquid phase [6,7].…”
Section: Resultsmentioning
confidence: 77%
“…Although conscientious efforts were made to follow all the experimental procedures and useful information obtained for future studies, the inter-ionic distance in the liquid phase was rather underestimated in comparison with the value derived from diffraction techniques [3][4][5] and the other XAFS study [10]. In the present work, our newly designed quartz cells were well adapted to obtain highly resolved spectra.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The decrease in coordination number for La-Cl pair from RT to 1173 K is thought to be due to the increase in molar volume and to be well interpreted by that on melting, for instance, 19.1% [29]. As pointed out in introduction section, Wasse and Salmon [10,11] reported that the CN of the first La-Cl correlation in molten LaCl 3 was 8.2. In contrast, the corresponding CN in solid LaCl 3 was 9, as described in [26].…”
Section: Xafsmentioning
confidence: 73%
“…However, another structural image has been recently proposed in neutron diffraction (ND) and molecular dynamics (MD) works. Wasse and Salmon [10,11] reported from systematic ND studies of molten rare-earth trichlorides that the CN of the first M-Cl correlation was not always fixed at 6; for example, that of molten LaCl 3 was 8.2. Hutchinson et al [12,13] obtained MD simulation results of some rare-earth trichloride melts by using a polarizable ionic model (PIM), which reproduced well the ND results by Wasse and Salmon.…”
Section: Introductionmentioning
confidence: 99%